تطور تعليم اللغة العربية بولاية أتشيه - Badruzzaman, Badruzzaman (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2022)
Aceh is one of the provinces in Indonesia where the majority of the population is Muslim. Islam and Arabic are like two sides of a coin that cannot be separated from each other, when Islam coming to Indonesia, started from province of Aceh, Arabic language developed with the beginning of Islam, Muslims had to learn the Arabic language to explore their religion. In this article, tries to describe the development of teaching Arabic in Aceh.